Avaliação dos reflexos da operação do virador de vagões em produção e na fila de trens para descarga de produtos - Willam Faria Guachalla (2012)
The use of simulation on increase capacity studies has been more intense over the past decade. In theory, this tool serves as a platform for the development of feasibility analyzes that precede the investments to be made. This dissertation presents the construction of a generic model for application in integrated chains based mining cycle trains, with application in a case study of a large Brazilian miner. The objective is to evaluate the consequences when simulated operational performance improvements in a car dumper - that is the main bottleneck of a chain integrated mine-railroad-port. The model uses Arena software version 13.0 as a platform for simulation and quantifies the variations of tonnage unloaded and queue of trains to discharge from the reduction of failures of the bottleneck, mapped during the year of 2011. The usefulness of the proposed research is confirmed when it is observed a lack of researchfocusing on issues related to the discharge of the railway, which knowledge can assist companies in their decision making. The results prove the efficiency of the proposed model, since it was possible to measure the consequences of each type of system downtime - inproduction and queue for unloading trains. Based on the proposed scenarios it was possible to identify the improvement plan that provides benefits for the best performance of the mining company during the year studied.